Maternal behavioral factors influencing postpartum weight retention. Clinical and metabolic implications - Falivene, Mariana Araceli (2017)
Objectives: to describe some factors of maternal behavior such as breastfeeding, diet, physical activity, sleep and clinical-metabolic disorders associated with retention and/or weight gain during postpartum. Methods: specific articles on the subject were searched in LILACS, MEDLINE/PubMed and SciELO databases. Results: the literature review suggests that breastfeeding or physical activity alone are not enough to return to the pre-pregnancy weight, if they are not combined with restrictions of energy intake. Reduced sleep affects both eating habits and activity patterns resulting in lower energy expenditure, in addition to altering the glycemic metabolism. Conclusions: maternal obesity increases the risk of metabolic syndrome. Interventions during postpartum are critical for maternal health and could be the key in reducing the risk of transgenerational maternal/childhood obesity.